Timing and Route of Contamination of Patient Rooms With Healthcare-Associated Pathogens. (October 2020) - Redmond, Sarah; Cadnum, Jennifer; Pearlmutter, Basya; Herrera, Natalia Pinto; Donskey, Curtis
Abstract : Background: Transmission of healthcare-associated pathogens such as Clostridioides difficile and methicillin-resistant Staphylococcus aureus (MRSA) is a persistent problem in healthcare facilities despite current control measures. A better understanding of the routes of pathogen transmission is needed to develop effective control measures. Methods : We conducted an observational cohort study in an acute-care hospital to identify the timing and route of transfer of pathogens to rooms of newly admitted patients with negative MRSA nares results and no known carriage of other healthcare-associated pathogens. Rooms were thoroughly cleaned and disinfected prior to patient admission. Interactions of patients with personnel and portable equipment were observed, and serial cultures for pathogens were collected from the skin of patients and from surfaces, including those observed to come in contact with personnel and equipment. For MRSA, spa typing was used to determine relatedness of patient and environmental isolates. Results: For the 17 patients enrolled, 1 or more environmental cultures became positive for MRSA in rooms of 10 patients (59%), for C. difficile in rooms of 2 patients (12%) and for vancomycin-resistant enterococci (VRE) in rooms of 2 patients (12%). The patients interacted with an average of 2.4 personnel and 0.6 portable devices per hour of observation. As shown in Figure 1, MRSA contamination of the floor occurred rapidly as personnel entered the room. In a subset of patients, MRSA was subsequently recovered from patients' socks and bedding and ultimately from the high-touch surfaces in the room (tray table, call button, bedrail). For several patients, MRSA isolates recovered from the floor had the same spa type as isolates subsequently recovered from other sites (eg, socks, bedding, and/or high touch surfaces). The direct transfer of healthcare-associated pathogens from personnel or equipment to high-touch surfaces was not detected. Conclusions: Healthcare-associated pathogens rapidly accumulate on the floor of patient rooms and can be transferred to the socks and bedding of patients and to high-touch surfaces. Healthcare facility floors may be an underappreciated source of pathogen dissemination not addressed by current infection control measures. Funding: None Disclosures: None